Experimental study on the stabilization of laterite soil with chitosan biopolymer for subgrade applications - Banne, Shailendra Pandurang; Ingle, Ganesh S.; Dhawale, Arun; Gaikwad, Siddharth; Bobade, Sudarshan (Engineering and Applied Science Research, 2025)
Laterite soil, commonly found in the Konkan region in Maharashtra, India, often needs better engineering properties, posing challenges for its use in construction. By adding chitosan, a naturally occurring biopolymer derived from chitin, the study aims to enhance the geotechnical properties of laterite soil. Both untreated and chitosan-treated laterite soil samples were subjected to various laboratory tests, including the California Bearing Ratio (CBR), compaction, Atterberg limits, and direct shear testing. The chitosan was added in varying percentages (0.15%, 0.30%, and 0.45 % by weight) to determine the optimal dosage for laterite soil stabilisation. As the chitosan concentration increases from 0% to 0.3%, the Maximum dry density (MDD) value increases from 1.41 gm/cc to 1.92 gm/cc; adding chitosan further slightly decreases the MDD. The un-soaked CBR value of laterite soil containing 0.30% chitosan biopolymer increased by 108.81%, while the soaked CBR value increased by 142.83%. The soil’s cohesiveness and internal friction angle increased by 120% and 15%, respectively, with the optimal dose of 0.30% chitosan. Utilising chitosan in T8 subgrade soil costs INR 6.48 crores, which is 2.57 times more than laterite soil, and requires a pavement depth of 1395 mm. In the case of T9 subgrade soil, at a depth of 1495 mm, the cost is INR 8.08 crores, which is 3.14 times more than that of laterite soil. This study highlights the potential of chitosan biopolymer as an eco-friendly and sustainable soil stabilizer for subgrade applications. It also offers a comprehensive cost-benefit analysis for pavement applications, demonstrating the financial feasibility of using chitosan biopolymer despite its higher initial costs.